Job Description of Family Planning Field Officers in the Decrease of Total Fertility Rate (TFR) in Population Control and Family Planning Department - Widia Astuti Tanjung; Heru Santosa; Kintoko Rochadi (Britain International for Academic Research (BIAR) Publisher, 2020)
Performance of Family Planning Field Officers can be seen by achieving the number of TFR, in accordance with the national target of 2.4. The total TFR of Sibolga city in 2016 was 2.6. Sibolga City is a city that consists of 4 districts and 17 villages. Sibolga City has 31 Family Planning Field Officers. The purpose of this study is to determine the performance of Family Planning Field Officers to reduce the total fertility rate. This type of research is qualitative with a phenomology approach. The results shows that the performance of Family Planning Field Officers in Population Control and Family Planning Department of Sibolga City PPKB Office is still not optimal. This is marked by the performance evaluation carried out and monitored only through social media chat groups, but the implementation of direct monitoring is still not good, there are gaps in report data in the field found by the difference in the number of Family Planning participants in the field with the number of Family Planning participants in Population Control and Family Planning Department Office, delays in sending reports, the number of human resources has exceeded the provisions but the TFR target has not been achieved, PLKB skills in counseling are still lacking, Population Control and Family Planning Department work discipline is still often violating things such as being late for work and leaving the workplace without a clear reason. This study recommends that Population Control and Family Planning Department conduct routine monitoring of Population Control and Family Planning Department in the Family Planning Health Center, provide training to PLKB in terms of counseling, give rewards to the districts with the lowest TFR, conduct scheduled outreach to the community regarding family planning programs in terms of reduction TFR number.